Tashkent - The Center of Islamic Civilization (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Tashkent occupies a special place in the socio-economic, cultural and spiritual development of Central Asia and has made a significant contribution to the centuries-old historical and evolutionary processes of development. In this place there are ruins of ancient Kangaroo settlements, in particular architectural monuments built in Tashkent in the Middle Ages, as well as many historical, archaeological and cultural monuments preserved in the city of Tashkent and its surroundings. The article provides information about scientists who lived in Tashkent in the Middle Ages and made a great contribution to the Islamic civilization.